2014
DOI: 10.1186/1745-6215-15-203
|View full text |Cite
|
Sign up to set email alerts
|

WELLFOCUS PPT – modified positive psychotherapy to improve well-being in psychosis: study protocol for a pilot randomised controlled trial

Abstract: BackgroundThe promotion of well-being is an important goal of recovery oriented mental health services. No structured, evidence-based intervention exists that aims to increase the well-being in people with severe mental illness such as psychosis. Positive psychotherapy (PPT) is a promising intervention for this goal. Standard PPT was adapted for use with people with psychosis in the UK following the Medical Research Council framework for developing and testing complex interventions, resulting in the WELLFOCUS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 58 publications
(70 reference statements)
3
44
0
1
Order By: Relevance
“…Data were collected as part of a larger randomized controlled pilot trial testing WELLFOCUS PPT (Schrank, Riches, et al, 2014). Inclusion criteria for the trial were age 18-65 years, clinical diagnosis of psychosis, sufficient conversational English, and ability to provide informed consent.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were collected as part of a larger randomized controlled pilot trial testing WELLFOCUS PPT (Schrank, Riches, et al, 2014). Inclusion criteria for the trial were age 18-65 years, clinical diagnosis of psychosis, sufficient conversational English, and ability to provide informed consent.…”
Section: Participantsmentioning
confidence: 99%
“…An adaptation of standard 14-session PPT (WELLFOCUS PPT) has been developed for people with psychosis Schrank, Riches, et al, 2013) and tested in a randomized controlled trial (Schrank, Riches, et al, 2014), which was found to improve specific aspects of well-being, including overall symptomatology and depression. The aim of this study was to investigate service user experience of therapy components in WELLFOCUS PPT.…”
mentioning
confidence: 99%
“…Schrank et al . () used PPT in people with psychosis, and found that it not only improved specific aspects of mental health, but also reduced symptoms of depression. Compared to standard therapeutic methods and antidepressants, PPT had a better long‐term effect on alleviating depression and increasing happiness (Asqharipoor et al .…”
Section: Introductionmentioning
confidence: 99%
“…The intervention was well accepted by the patients and associated with improvements in psychological well-being, psychological recovery, self-esteem, and psychiatric symptoms. Recently, PPT was evaluated in a randomized controlled trial for people with psychosis (Schrank et al, 2014). In an iterative process with experts an adapted version of PPT was developed, called WELLFOCUS PPT (Riches, Schrank, Rashid, & Slade, 2015).…”
Section: Et Bohlmeijer L Bolier Sma Lamers and Gj Westerhofmentioning
confidence: 99%